Furan copolyesters containing itaconic acid-based pyrrolidone structures, and methods and uses thereof
Patent Information
- Application Number
- CN202611127901.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-09-29
AI Technical Summary
这些路线能够在一定程度上降低结晶度或提高水解速率,但通常缺少兼顾材料使用性能与外部光照后质量损失的结构设计
与未改性PEF相比,本发明通过C11-DE引入的长脂肪链间隔基和吡咯烷酮环降低呋喃-乙二醇链段的规整堆积,使玻璃化转变温度由约85℃降低至24-79℃范围内,并使薄膜断裂伸长率由4.5%提高至60.0%、韧性由1.9 MJ/m3提高至14.9 MJ/m3。
Smart Images

Figure CN122832260A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of bio-based polyester materials technology, specifically relating to a furan copolyester containing an itaconic acid pyrrolidone structure, its preparation method, and its application in products that can be treated with ultraviolet light in aqueous phase and aerobically biodegraded. Background Technology
[0002] Poly(ethylene 2,5-furandicarboxylate) (PEF) is typically obtained by polymerizing biomass-derived 2,5-furandicarboxylic acid or its diester with ethylene glycol, and is one of the important bio-based alternatives to polyethylene terephthalate (PET). Due to the rigid and nonlinear structure of the furan ring, PEF exhibits a high glass transition temperature, good mechanical strength, and gas barrier properties; studies have reported that PEF's barrier properties against O2 and CO2 are approximately 10 times and 4 times that of PET, respectively.
[0003] However, the rigidity of the furan rings in the PEF backbone and the relatively dense chain stacking also result in a low rate of hydrolysis and biodegradation in ambient water and conventional microbial environments. At the same time, unmodified PEF usually exhibits brittleness with high modulus and low elongation at break, which limits its application in flexible packaging, agricultural films and products requiring environmental end-of-life treatment.
[0004] Existing technologies have attempted to improve the flexibility and degradation behavior of PEF by introducing aliphatic diacids, diols, or other copolymer components. These approaches can reduce crystallinity or increase hydrolysis rates to some extent, but they typically lack structural designs that balance material performance with mass loss after external light exposure. Itaconic acid can react with amino compounds to form N-substituted pyrrolidone structures, which can be introduced into polymer materials as bio-based heterocyclic units. However, how to integrate the itaconic acid-based pyrrolidone structure with the PEF backbone while considering thermal processing stability, improved toughness, mass loss after UV-guided aqueous treatment, and subsequent aerobic biodegradation still requires reproducible implementation schemes that consider structural design, preparation conditions, and performance verification. Summary of the Invention
[0005] Technical problems to be solved The present invention aims to provide a PEF-based furan copolyester that, while maintaining the thermal processing stability of PEF, introduces diester monomers containing itaconic acid-based pyrrolidone structures and long aliphatic chain spacers through copolymerization, thereby reducing the glass transition temperature and crystallinity regularity of the material, improving the elongation at break, and causing mass loss after exposure to ultraviolet light in an aqueous environment, thus promoting subsequent aerobic biodegradation.
[0006] Technical solution To achieve the above objectives, the present invention provides a furan copolyester containing an itaconic acid-based pyrrolidone structure, which is a copolyester formed from 2,5-furandicarboxylic acid or dimethyl 2,5-furandicarboxylate, ethylene glycol, and methyl 11-[4-(methoxycarbonyl)-2-oxopyrrolidone-1-yl]undecanoate. The diester monomer is abbreviated as C11-DE. The main chain of the copolyester comprises ethylene glycol 2,5-furandicarboxylate structural units and diester structural units containing pyrrolidone rings formed by C11-DE.
[0007] In a preferred embodiment, the molar percentage of the diester structural units formed by C11-DE relative to the total amount of structural units formed by 2,5-furandicarboxylic acid or its diester and the diester structural units formed by C11-DE is 5-50 mol%; during preparation, the C11-DE feed ratio is 5-50 mol%, for example 5 mol%, 10 mol%, 20 mol%, or 50 mol%. The resulting copolyester can be denoted as C11-X-PEF, where X represents the molar percentage of the diester structural units formed by C11-DE, and the preparation stage can correspond to the molar percentage of C11-DE feed.
[0008] The present invention also provides a preparation method, comprising first preparing C11-DE from itaconic acid and 11-aminoundecanoic acid, then mixing C11-DE with 2,5-furandicarboxylic acid or dimethyl 2,5-furandicarboxylate, ethylene glycol and a polycondensation catalyst, and carrying out a melt reaction under an inert atmosphere; esterification is carried out when 2,5-furandicarboxylic acid is used, transesterification is carried out when dimethyl 2,5-furandicarboxylate is used, followed by a polycondensation reaction.
[0009] Beneficial effects Compared to unmodified PEF, this invention reduces the orderly packing of furan-ethylene glycol segments by introducing long aliphatic chain spacers and pyrrolidone rings via C11-DE, thereby lowering the glass transition temperature from approximately 85°C to the range of 24-79°C, and increasing the film elongation at break from 4.5% to 60.0% and toughness from 1.9 MJ / m. 3 Increased to 14.9 MJ / m 3 .
[0010] The examples show that the copolyester of the present invention still maintains high thermal stability, and the 5% thermal weight loss temperature of each C11-X-PEF sample is not lower than 394°C, which can meet the requirements of conventional melt processing for thermal stability.
[0011] The examples also show that copolyesters containing pyrrolidone structures undergo observable mass loss under the combined action of ultraviolet light and aqueous media; C11-50-PEF retained approximately 89.5% of its mass in a 20-day light-exposed aqueous environment, lower than the approximately 100% retention of unmodified PEF. C11-50-PEF pretreated with ultraviolet light exhibited a degradation rate of approximately 60% in aerobic BOD tests after 21 days, higher than the approximately 45% degradation rate of the untreated sample. These data are shown in Tables 5 and 6, respectively. Attached Figure Description
[0012] Figure 1 This is a schematic diagram of an exemplary synthetic route for preparing iPEF furan copolyester using dimethyl 2,5-furandicarboxylate as the furan feedstock and C11-DE as the participant.
[0013] Figure 2 This is a schematic diagram of the proton NMR spectrum and proton assignment of a representative iPEF copolyester.
[0014] Figure 3 The TGA and DTG thermal analysis curves of unmodified PEF and C11-X-PEF copolyesters under nitrogen atmosphere are shown.
[0015] Figure 4 The second heating curves of DSC for unmodified PEF and C11-X-PEF copolyesters are shown.
[0016] Figure 5 The stress-strain curves are for unmodified PEF and C11-X-PEF copolyester films.
[0017] Figure 6 The mass retention curves of unmodified PEF and C11-X-PEF copolyesters in aqueous media under continuous ultraviolet light irradiation are shown.
[0018] Figure 7 The aerobic biodegradation curves of microcrystalline cellulose, untreated C11-50-PEF, and UV-treated C11-50-PEF in activated sludge are shown. Detailed Implementation
[0019] Table 1. Definitions of Terms
[0020] In this paper, Mn is the number-average molecular weight, Mw is the weight-average molecular weight, and PDI is the dispersion coefficient, all determined by GPC; Td5 is the 5% thermogravimetric temperature, and Tdo is the initial thermal decomposition temperature, both determined by TGA; Tg is the glass transition temperature, Tm is the melting point, and ΔHm is the enthalpy of fusion, all determined by the second heating curve of DSC; E is Young's modulus, σ is tensile strength, ε is elongation at break, and ω is strain energy density, all obtained by uniaxial tensile testing at room temperature.
[0021] Example 1: Preparation of C11-DE monomer Equimolar amounts of itaconic acid and 11-aminoundecanoic acid were added to a round-bottom flask, stirred, and heated to 120 °C for 24 h. After cooling to room temperature, excess methanol and trimethylchlorosilane (TMSCl) were added, and the mixture was stirred at room temperature for 48 h. Subsequently, methanol and TMSCl were removed under reduced pressure to obtain a white powdery crude product. The crude product was washed repeatedly with deionized water and dried under vacuum at 40 °C for 24 h to obtain the C11-DE monomer.
[0022] The actual yield of C11-DE was 95%, and the purity reached 99.5% (purity determination method is as follows). 1 ¹H-NMR (purity calculated by integral area normalization of monomer dissolved in deuterated DMSO). 1 The original H NMR spectrum can be found in... Figure 2 Its Chinese name is methyl 11-[4-(methoxycarbonyl)-2-oxopyrrolidin-1-yl]undecanoate, and its English name is methyl 11-[4-(methoxycarbonyl)-2-oxopyrrolidin-1-yl]undecanoate.
[0023] Example 2: Preparation of C11-X-PEF furan copolyester A predetermined molar ratio of 2,5-furandicarboxylic acid or dimethyl 2,5-furandicarboxylate, ethylene glycol, C11-DE, and a polycondensation catalyst is added to a reactor equipped with a high-torque mechanical stirrer. After complete purging with nitrogen, the reaction system is heated to 180°C under nitrogen protection and stirred for 24 h. When 2,5-furandicarboxylic acid is used, esterification occurs; when dimethyl 2,5-furandicarboxylate is used, transesterification occurs, followed by polycondensation and / or chain exchange reactions. In a specific example of C11-10-PEF preparation, 2,5-furandicarboxylic acid or dimethyl 2,5-furandicarboxylate is used as the furan feedstock, and the molar ratio of the furan feedstock, ethylene glycol, C11-DE, and Sb₂O₃ is 9:20:1:0.01. The reaction system can then be evacuated to an absolute pressure below 50 Pa to promote the removal of small molecule byproducts and the polycondensation reaction. After the reaction was complete, the molten copolyester was discharged and cooled to room temperature to obtain C11-X-PEF copolyester. When determining the number-average molecular weight, weight-average molecular weight, and dispersion index using GPC, HFIP could be used as the mobile phase at a flow rate of 1.0 mL / min and a column temperature of 35℃. A calibration curve was established using narrow-distribution PMMA standard samples. Table 2 lists the GPC results for each sample.
[0024] Table 2. Feed ratio of C11-X-PEF to PEF and GPC results
[0025] Example 3: Structural Characterization
[0026] iPEF samples were analyzed using a 600 MHz nuclear magnetic resonance spectroscopy (NMR) spectrometer. Due to the limited solubility of furan polyesters in common solvents, the samples were dissolved in deuterated trifluoroacetic acid (TMS) as an internal standard. In representative spectra, the signal at δ=7.25 ppm was attributed to a proton in the 2,5-substituted furan ring; the signal at δ=4.91 ppm was attributed to a methylene group esterified with ethylene glycol; pyrrolidone ring and adjacent nitrogen atom methylene proton signals appeared in the regions of δ=4.50-4.80 ppm and δ=3.50-4.30 ppm; signals at δ=2.60 ppm and δ=3.30 ppm were attributed to methylene groups adjacent to ester or amide carbonyl groups; the signal at δ=1.70 ppm was attributed to a β-methylene group; and the strong peak near δ=1.30 ppm was attributed to an internal methylene group within the C11 long aliphatic chain. These signals collectively demonstrate that the furan structure, ethylene glycol structure, and pyrrolidone-containing long aliphatic chain structure are all incorporated into the copolyester. The content of diester structural units formed by C11-DE can be calculated based on the integral ratio of the proton of the furan ring to the characteristic peak of the C11 long fatty chain. The measured content is consistent with the feed ratio.
[0027] Example 4: Thermal and Mechanical Properties The Td5 and initial thermal decomposition temperature of each sample were obtained by heating from 30℃ to 800℃ at a rate of 10℃ / min under a nitrogen atmosphere using thermogravimetric analysis (TGA). DSC was used under a nitrogen flow for a first heating, cooling, and a second heating. An exemplary procedure was to heat from 30℃ to 300℃, cool to 30℃, and then heat again to 300℃, with both heating and cooling rates at 10℃ / min. The second heating curve was used to determine Tg and Tm. The thermal and mechanical properties are shown in Tables 3 and 4, respectively. Room temperature uniaxial tensile tests were performed using hot-pressed thin films. The sample size was 2 cm × 5 cm, with a typical thickness of approximately 0.1 mm. The tensile speed was 10 mm / min, and at least 5 independent samples were tested in each group. The mean and standard deviation were calculated.
[0028] Table 3 Thermal performance parameters of C11-X-PEF and PEF
[0029] Table 4 Mechanical property parameters of C11-X-PEF and PEF films
[0030] Example 5: Performance of UV-treated aqueous phase 5.0 g of polymer sample was placed in a quartz petri dish, and 10 mL of artificial seawater was added to immerse the sample in the aqueous medium. The sample was then continuously irradiated with a 240-420 nm high-pressure mercury lamp at a power density of 25 mW / cm³. 2 Samples were taken out every 24 hours, washed with deionized water to remove residual salts, and vacuum dried at 40°C to constant weight. The mass retention rate was calculated by gravimetric method. Each experiment was repeated three times, and the average value was taken. The mass retention rates after 20 days are shown in Table 5.
[0031] Table 5. Mass retention rates of C11-X-PEF and PEF in aqueous media after 20 days of illumination.
[0032] Without being limited by a specific mechanism, under illumination, the pyrrolidone ring and its adjacent carbonyl structure may serve as photoresponsive sites, promoting the formation of low molecular weight fragments with high polarity in the material; the low Tg and high free volume caused by the long aliphatic chain are conducive to the entry of water molecules into the polymer, which may be beneficial to hydrolysis and fragment precipitation; this mechanism explanation does not constitute a limitation on specific photochemical reaction pathways.
[0033] Example 6: Aerobic Biodegradation Performance BOD testing was performed using a closed-loop respiration meter system according to ISO 14851. Pretreated activated sludge was diluted with standard mineral salt medium to a suspended solids concentration of approximately 100 mg / L as inoculum. A copolyester sample equivalent to approximately 100 mg of theoretical oxygen demand was added to a sealed bottle containing 250 mL of inoculum medium. Microcrystalline cellulose served as a positive control, and the inoculum medium as a blank control. KOH was placed at the bottle neck to absorb the generated CO2. The reaction flask was incubated at 25±1℃ in the dark with continuous stirring for 28 days. The cumulative oxygen consumption was automatically recorded, and the degradation rate was calculated as the ratio of the net BOD (sample BOD minus blank BOD) to the theoretical oxygen demand. Three parallel tests were conducted.
[0034] BOD testing was performed on C11-50-PEF samples. The positive control microcrystalline cellulose showed a degradation rate of approximately 88% at 21 days. The degradation rate of C11-50-PEF without UV pretreatment was approximately 45% at 21 days; the degradation rate of the UV-pretreated samples continued to increase after an adaptation period of approximately 1.5 days, reaching 50% at approximately day 9 and approximately 60% at day 21. The corresponding data are shown in Table 6.
[0035] Table 6. Degradation rate of C11-50-PEF in 21-day BOD test
[0036] The above results indicate that, within the tested feed ratio ranges of 5 mol%, 10 mol%, 20 mol%, and 50 mol%, after introducing the structural units formed by C11-DE, the resulting furan copolyester maintained a thermal weight loss temperature of no less than 394℃, and exhibited increased film elongation at break and mass loss after UV-treated aqueous phase with increasing C11-DE feed ratio. Among them, the degradation rate of C11-50-PEF after UV-treated aqueous phase in the 21-day BOD test was higher than that of the sample without UV pretreatment.
Claims
1. A furan copolyester containing an itaconic acid-based pyrrolidone structure, characterized in that, The furan copolyester is a copolyester formed by esterification or transesterification and polycondensation of 2,5-furandicarboxylic acid or dimethyl 2,5-furandicarboxylic acid, ethylene glycol, and diester monomers containing itaconic acid pyrrolidone structures; wherein esterification is performed when 2,5-furandicarboxylic acid is used, and transesterification is performed when dimethyl 2,5-furandicarboxylic acid is used; the main chain of the furan copolyester comprises ethylene glycol 2,5-furandicarboxylic acid ester structural units and diester structural units containing pyrrolidone rings formed from the diester monomers; the diester monomer is methyl 11-[4-(methoxycarbonyl)-2-oxopyrrolidone-1-yl]undecanoate; wherein the molar percentage of the diester structural units containing pyrrolidone rings in all diacid / diester structural units is 5-50 mol.
2. The furan copolyester according to claim 1, characterized in that, The furan copolyester is formed by transesterification and polycondensation of dimethyl 2,5-furandicarboxylate, ethylene glycol, and the diester monomer.
3. The furan copolyester according to claim 1 or 2, characterized in that, The molar percentage of the diester structural unit containing the pyrrolidone ring is 5 mol%, 10 mol%, 20 mol%, or 50 mol.
4. The furan copolyester according to any one of claims 1-3, characterized in that, The number-average molecular weight of the furan copolyester was determined to be 0.7 × 10⁻⁶ by gel permeation chromatography. 4 -2.9×10 4 g / mol, weight-average molecular weight is 1.5 × 10⁻⁶ g / mol 4 -5.2×10 4 g / mol, with a molecular weight distribution coefficient of 1.5-2.
4.
5. The furan copolyester according to any one of claims 1-4, characterized in that, The furan copolyester has a 5% thermal weight loss temperature of not less than 394°C, a glass transition temperature of 24-79°C, and a melting point of 181-210°C.
6. The furan copolyester according to any one of claims 1-5, characterized in that, The film formed by hot pressing the furan copolyester has an elongation at break of 6.0-60.0% and a tensile strength of 25-78 MPa when subjected to uniaxial tensile testing at 23±2℃.
7. An article characterized in that, The product comprises the furan copolyester according to any one of claims 1-6; the product is a film formed by hot pressing the furan copolyester.
8. A method for preparing the furan copolyester according to any one of claims 1-6, characterized in that, include: 2,5-furandicarboxylic acid or dimethyl 2,5-furandicarboxylate, ethylene glycol, methyl 11-[4-(methoxycarbonyl)-2-oxopyrrolidine-1-yl]undecanoate, and a polycondensation catalyst are mixed and melt-reacted at 180°C under an inert atmosphere. When 2,5-furandicarboxylic acid is used, esterification occurs; when dimethyl 2,5-furandicarboxylate is used, transesterification occurs. The reaction system pressure is then reduced to no more than 100 Pa and polycondensation is carried out to obtain the furan copolyester.
9. The method according to claim 8, characterized in that, The melting reaction includes: stirring at 180°C for 24 h under a nitrogen atmosphere, wherein esterification is performed using 2,5-furandicarboxylic acid, and transesterification is performed using dimethyl 2,5-furandicarboxylate. Subsequently, the pressure of the reaction system is reduced to below 50 Pa, and polycondensation and / or chain exchange reactions are continued. The polycondensation catalyst is antimony trioxide. The diester monomer is prepared by the following steps: equimolar amounts of itaconic acid and 11-aminoundecanoic acid are mixed and reacted at 120°C for 24 h. After cooling to room temperature, excess methanol and trimethylchlorosilane are added and reacted at room temperature for 48 h for esterification. The mixture is washed and dried under vacuum at 40°C for 24 h to obtain methyl 11-[4-(methoxycarbonyl)-2-oxopyrrolidine-1-yl]undecanoate.
10. A method for ultraviolet light aqueous phase treatment of the furan copolyester according to any one of claims 1-6, characterized in that, The furan copolyester or an article containing the furan copolyester is placed in an aqueous medium and irradiated with ultraviolet light of wavelength 240-420 nm; wherein the aqueous medium is artificial seawater and the ultraviolet light power density is 25 mW / cm². 2 .